DETERMINAN PERILAKU GENERASI ZILENIAL DAN MILENIAL DALAM MENGGUNAKAN E COMMERCE DENGAN PENDEKATAN MODEL COMBINATION TPB-TAM: Determinan Perilaku Generasi Zilenial Dan Milenial Dalam Menggunakan E Commerce Dengan Pendekatan Model Combination TPB-TAM - haeruddin (JOURNAL ISLAMIC ECONOMICS AD DIWAN, 2025)
The rapid development of technology has transformed conventional trading systems into e-commerce, enabling efficiency and ease in digital transactions. The advancement of technology, especially in commerce, has been widely accepted by all levels of society, particularly the Zilenial and Millennial generations, which naturally impacts consumer behavior. This study aims to determine the behavioral determinants of the Zilenial and Millennial Generations in using e-commerce through the TPB-TAM Combination Model approach. This research adopts a quantitative method, with the population consisting of the Zilenial and Millennial Generation (aged 11–42 years) at the AL-Ijtihad Al-Mahsuni Lotim Foundation. Data collection is conducted through questionnaires, and data analysis is performed using SmartPLS3. The study's results indicate that: (1) Attitude Towards Use (ATU) positively influences Intention to Use (BI); (2) Subjective Norms (SN) positively influence Intention to Use (BI); (3) Perceived Behavioral Control (PBC) does not significantly influence Intention to Use (BI); (4) Perceived Benefits (PU) positively influence Intention to Use (BI); and (5) Perceived Ease of Use (PEU) positively influences Intention to Use (BI). The findings confirm the proposed hypotheses, showing that ATU, SN, PU, and PEU have a positive and significant impact on BI, while PBC does not significantly affect BI. These results provide a deeper understanding of the role of technology in buying and selling transactions, particularly in e-commerce, and its influence on the behavioral patterns of the Zilenial and Millennial generations in adopting e-commerce.